2012
DOI: 10.2139/ssrn.972670
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Political Donations: Investment or Agency?

Abstract: We examine corporate donations to political candidates for federal offices in the United States from 1991 to 2004. Firms that donate have operating characteristics consistent with the existence of a free cash flow problem, and donations are negatively correlated with returns. A $10,000 increase in donations is associated with a reduction in annual excess returns of 7.4 basis points. Worse corporate governance is associated with larger donations. Even after controlling for corporate governance, donations are as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
114
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(116 citation statements)
references
References 31 publications
2
114
0
Order By: Relevance
“…A number of studies provide evidence consistent with the value-enhancement theory, showing a negative effect on firm value when politicians tied to the firm lose power and a positive effect when the connected politicians get elected (Faccio & Parsley, 2009;Jayachandran, 2006;Cooper, Gulen & Ovtchinnikov, 2010;Goldman, Rocholl, & So, 2009). Other evidence is more in line with the agency theory: political donations are negatively associated with returns (Faccio, 2010;Aggarwal et al, 2012) and political donations in the US are associated with a free cash flow problem, worse corporate governance, and a higher number of poor acquisitions (Duchin & Sosyura, 2012).…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…A number of studies provide evidence consistent with the value-enhancement theory, showing a negative effect on firm value when politicians tied to the firm lose power and a positive effect when the connected politicians get elected (Faccio & Parsley, 2009;Jayachandran, 2006;Cooper, Gulen & Ovtchinnikov, 2010;Goldman, Rocholl, & So, 2009). Other evidence is more in line with the agency theory: political donations are negatively associated with returns (Faccio, 2010;Aggarwal et al, 2012) and political donations in the US are associated with a free cash flow problem, worse corporate governance, and a higher number of poor acquisitions (Duchin & Sosyura, 2012).…”
mentioning
confidence: 55%
“…However, political giving may also reflect the personal political preferences of managers and benefit their personal career. Consistent with this idea, the literature shows that firms giving more to politics are associated with fraudulent behavior, free cash flow problems, bad corporate governance, and lower returns (Aggarwal et al, 2012;Duchin & Sosyura, 2012;Faccio, 2010;Yu & Yu, 2011). We empirically test the competing theories by means of a difference-in-differences approach applied to the 2010 general elections in the UK where virtually all political contributions have to be disclosed.…”
Section: Hypothesis Developmentmentioning
confidence: 93%
See 1 more Smart Citation
“…Goldman, Rocholl, and So (2010) also document the real effects of political connections on corporate financial decisions and show that politically connected firms have preferential access to government procurement contracts. Others, such as Aggarwal, Meschke, and Wang (2011), argue that political activism is indicative of agency problems and show that firms with high political contributions experience lower risk-adjusted returns. Our evidence suggests that political connections serve as an insurance mechanism against extreme events.…”
Section: Related Literaturementioning
confidence: 99%
“…Political connections, allow connected firms to gain advantage from various governmental interferences, such as preferential access to government and private financing, lower tax rates, and bailout opportunities (Faccio, 2006;Claessens, Feijen, & Laeven, 2008;Wu, Wu, Zhou, & Wu, 2012;Goldman, Rocholl, & So, 2013). It has also been documented that political connections becomes expensive due to rent-seeking by politician(s) (Aggarwal, Meschke, & Wang, 2012). Boubakri, Ghoul, and Saffar (2013) reported that due to close relationship of a politically connected firm and politician(s), the firm may fulfill political goals by using firm and their resources which ultimately contradicts profit and wealth maximization objectives of the firm.…”
Section: Introductionmentioning
confidence: 99%